Enhanced rate capability for asymmetric supercapacitors by binder-free Zn-Ni-Co oxide nanoflakes on Ni foam. (May 2021) - Ali, Awais; Hameed, Iqra; Ammar, Muhammad; Mujahid, Rana; Mirza, Shahid
Highlights: A binder-free Zn-Ni-Co oxides @NF was prepared and as-prepared electrode material showed a rate capability of 74.5% at 25 A g −1 . Negligible loss in Cs (0.00132 F g −1 ) after each GCD (10, 000) cycle. ASC showed the Cs 123 Fg −1 with 82% retained after 10, 000 cycles. ASC showed the maximum energy density and power density of 41 Wh Kg −1 and 6869 W kg −1 respectively. Abstract: 3D hierarchical nanostructure of Zn-Ni-Co oxide is grown on Ni foam (NF) using a hydrothermal reaction. Excellent dimensional stability and structural features, less contact resistance because of direct growth, and high electrical conductivity due to synergetic effects have made it a perfect candidate for binder-free electrode material. Zn-Ni-Co oxide show superior specific capacitance of 1837 F g −1 at 1 A g −1 with an excellent rate capability of 74.5% at 25 A g −1 . Up to 10, 000 galvanic charge-discharge (GCD) cycles, a negligible loss of about 0.00132 F g −1 in specific capacitance is observed after each GCD cycle in 3 M KOH electrolyte. The asymmetric supercapacitor (ASC) device is fabricated by activated carbon (AC) as negative and Zn-Ni-Co oxide as positive electrode material. Fabricated ASC device (Zn-Ni-Co oxide @NF//AC@NF) shows a specific capacitance of 123 F g −1 at 1 A g −1 with capacitance retention of 82% after 10, 000 GCD cycles and potential window of 1.55 V. A maximum specific power of 6869 W kg −1 at 20.99 Wh kg −1 and specific energy of 41 Wh kg −1 at 824.5 W kg −1 is observed. The astounding electrochemical performance of the 3D hierarchical nanostructure of Zn-Ni-Co oxide electrode material indicates a promising candidate for efficient energy storage applications.